Designed Single Atom Bifunctional Electrocatalysts for Overall Water Splitting: 3d Transition Metal Atoms Doped Borophene Nanosheets. Issue 24 (18th November 2020) - Xu, Mingxia; Zhang, Xiuyun; Liu, Yaqi; Zhao, Xinli; Liu, Yongjun; Wu, Ruchun; Wang, Jinlan
Abstract: Single atom catalysts (SAC) for water splitting hold the promise of producing H2 in a highly efficient and economical way. As the performance of SACs depends on the interaction between the adsorbate atom and supporting substrate, developing more efficient SACs with suitable substrates is of significance. In this work, inspired by the successful fabrications of borophene in experiments, we systematically study the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) activities of a series of 3 d transition metal‐based SACs supported by various borophene monolayers (BMs=α_sheet, α1 _sheet, and β1 _sheet borophene), TM/BMs, using density functional theory calculations and kinetic simulations. All of the TM/BMs systems exhibit superior HER performance compared to Pt with close to zero thermoneutral Gibbs free energy (ΔGH* ) of H adsorption. Furthermore, three Ni‐deposited systems, namely, Ni/α_BM, Ni/α1 _BM and Ni/β1 _BM, were identified to be superior OER catalysts with remarkably reduced overpotentials. Based on these results, Ni/BMs can be expected to serve as stunning bifunctional electrocatalysts for water splitting. This work provides a guideline for developing efficient bifunctional electrocatalysts. Abstract : Low potential ? Three types of TM/BMs systems were constructed by loading 3 d TM (TM=Sc−Ni) atoms on different borophene monolayers (BMs). The TM atoms display favorable catalytic performance (ΔGH* ∼0) for HER with the B atoms as highly active sites. Ni‐doped BMs are found to be excellent bifunctional catalysts, exhibiting remarkable OER performance with computed overpotentials of 0.34–0.48 V.